PENERAPAN ARSITEKTUR ISLAM PADA RANCANGAN RUMAH SAKIT ISLAM GORONTALO - Ilham Mu'ani; Zuhriati A. Djailani; Niniek Pratiwi (JAMBURA Journal of Architecture, 2023)
ABSTRACT. Gorontalo Islamic Hospital is a type D general hospital as part of a social organization located on Jalan Prof. HB. Jassin in Gorontalo City. This hospital serves patients both from Gorontalo City and from outside of it. However, the current hospital facilities are inadequate, particularly for inpatient facilities, both in terms of buildings and indoor facilities. According to one of the hospital staff/employees, several buildings are old, one of which is the inpatient building, so leaks often occur when raining. Additionally, many other problems emerge, such as the absence of parking facilities, narrow and hot emergency rooms, too narrow circulation among buildings/corridors, absence of eye care and hemodialysis facilities, and often clogged drains. In reference to these problems, it is indispensable to redesign the Gorontalo Islamic Hospital using a quantitative method based on measurement results in the form of standard results for room size and hospital capacity. Also, it employs qualitative methods in the form of words that contain meaning, instead of numbers, esppecially in the form of any theory or information, standard hospital room facilities, hospital room activities, and room function requirements. The Gorontalo Islamic Hospital was redesigned by directed it to the concept of Islamic Architecture, which employed three principles, including Habluminallah (the human relationship with Allah SWT), Habluminannas (the human relationship with fellow human beings) and Habluminal'alam (the human relationship with nature). The application of Islamic Architecture was also Motivated by the fact that it was in accordance with the Vision of the Gorontalo Islamic Hospital, namely "To become the first and leading Hospital of Gorontalo with quality services in accordance with Islamic values". Keywords: Islamic Hospital, Islamic Architecture, Gorontalo ABSTRAK. Rumah sakit Islam Gorontalo merupakan rumah sakit umum organisasi sosial tipe D yang berada di jalan Prof. HB. Jassin, Kota Gorontalo. Rumah sakit ini melayani pasien baik dari Kota Gorontalo maupun dari luar Kota Gorontalo. Akan tetapi, untuk fasilitas rumah sakit saat ini belum memadai terutama untuk fasilitas rawat inap baik dari segi bangunan maupun fasilitas dalam ruangannya. Menurut salah satu staf/pegawai rumah sakit ada beberapa fasilitas gedung yang sudah tua salah satunya gedung rawat inap sehingga sering terjadi kebocoran apabila saat hujan datang dan masih banyak permasalahan lain seperti tidak ada fasilitas untuk parkir, ukuran ruang gawat darurat terlalu sempit dan panas, sirkulasi antar gedung/koridor terlalu sempit, tidak ada fasilitas perawatan mata, tidak ada fasilitas hemodialisa, serta saluran air dan pembuangan sering tersumbat.Melihat permasalahan tersebut maka Rumah Sakit Islam Gorontalo perlu dirancang kembali dengan menggunakanmetode kuantitatif yang berdasarkan hasil pengukuran berupa hasil standar untuk ukuran ruangan dan kapasitas rumah sakit, dan juga menggunakan metode kualitatif yang berupa kata-kata yang mengandung makna bukan angka, khususnya berupa segala teori atau informasi, standar fasilitas ruang rumah sakit, kegiatan ruang rumah sakit dan kebutuhan fungsi ruang.Dalam merancang kembali Rumah Sakit Islam Gorontalo diarahkan pada konsep Arsitektur Islam yang menggunakan tiga prinsip yaitu prinsip Habluminallah, Habluminannas dan Habluminal’alam. Penerapan Arsitektur Islam ini juga dikarenakan sesuai dengan Visi Rumah Sakit Islam Gorontalo yaitu “Menjadi Rumah Sakit Pilihan pertama dan terkemuka di Gorontalo dengan pelayanan yang berkualitas berdasarkan nilai-nilai Islami”. Kata Kunci: Rumah Sakit Islam, Arsitektur Islam, Gorontalo